The applicability of Porter's generic strategies in pure online firms: A case study approach1. (25th April 2019) - Firoz Suleman, Marwa; Rashidirad, Mona; Firoz Suleman, Saffa
Abstract: The aim of this paper is to investigate the usability and applicability of Porter's generic strategies in the current e‐business environment. In this paper, a review of Porter's generic strategies was conducted to recognise the limitations and weaknesses of the model, which prevent its effective application in the e‐business environment. To do so, a case study approach on three pure online firms, e.g., Amazon, e‐bay and Google was employed. The findings acknowledged the application of Porter's generic strategies to pure online firms in order to achieve competitive advantage and proved the positive impact of generic strategies on firms' performance. The paper suggests that although cost leadership strategy is able to generate greater performance, pursuing a differentiation strategy can be more worthwhile and sustainable for pure online firms compared to cost leadership strategy. This research contributes to existing research by suggesting Porter's generic strategies as a valid and viable model for pure online firms which operate in the current e‐business environment.